Difference Analysis of modern market and traditional market strategy based on layout and quality of service. - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aimed to compare the traditional markets and modern markets in term of the layout and quality of service. The result of this study will be useful for governments and agencies involved in the development of traditional markets, and can make improvements in terms of the layout and quality of service.